1997
DOI: 10.1093/oxfordjournals.jbchem.a021837
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Substrate Binding Site and Carboxyl Terminal Region of Vacuolar H+-Pyrophosphatase of Mung Bean with Peptide Antibodies

Abstract: Vacuolar H+-translocating inorganic pyrophosphatase is a single-protein enzyme and uses a simple substance as an energy donor. Functional domains of the enzyme were investigated by using antibodies specific to peptides corresponding to the putative substrate-binding site (DVGADLVGKVE) in the hydrophilic loop and the carboxyl terminal part. The antibody to the former peptide clearly reacted with the pyrophosphatases of different plant species, and strongly inhibited the hydrolytic activity of the purified enzym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 42 publications
5
51
0
Order By: Relevance
“…Enrichment of plasma membrane proteins in the upper phase was verified by protein gel blot analysis using an antibody against the plasma membrane ATPase AHA2 (DeWitt et al, 1996), while enrichment of endosomal membrane proteins in the lower fraction was confirmed by detection of DET3, a subunit of the vacuolar ATPase (Schumacher et al, 1999) and of the vacuolar pyrophosphatase (VPPase; Takasu et al, 1997). Probing of these fractions with the AMT1;2 antibody showed that in both cases, AMT1;2 was enriched in the upper phase (Figure 3).…”
Section: Subcellular Localization Of Amt1;2mentioning
confidence: 98%
See 1 more Smart Citation
“…Enrichment of plasma membrane proteins in the upper phase was verified by protein gel blot analysis using an antibody against the plasma membrane ATPase AHA2 (DeWitt et al, 1996), while enrichment of endosomal membrane proteins in the lower fraction was confirmed by detection of DET3, a subunit of the vacuolar ATPase (Schumacher et al, 1999) and of the vacuolar pyrophosphatase (VPPase; Takasu et al, 1997). Probing of these fractions with the AMT1;2 antibody showed that in both cases, AMT1;2 was enriched in the upper phase (Figure 3).…”
Section: Subcellular Localization Of Amt1;2mentioning
confidence: 98%
“…Blots were developed using the ECL Advance Western Blotting Detection Kit (Amersham) according to the manufacturer's protocol. Primary antibodies and the secondary antibody (peroxidase-linked anti-rabbit IgG; Amersham) were diluted in blocking solution at the following concentrations and combinations: anti-AMT1;1 at 1:400 with secondary antibody at 1:25,000, anti-AMT1;2 at 1:10,000, anti-AMT1;3 at 1:5000, anti-AMT2;1 at 1:4000, anti-AHA2 at 1:10,000 (DeWitt et al, 1996), anti-VPPase (Takasu et al, 1997) at 1;2000, and anti-DET3 at 1:20,000 (Schumacher et al, 1999) with secondary antibody at 1:10,000. MagicMark Western Standard (Invitrogen) was used as molecular weight marker.…”
Section: Protein Gel Blot Analysismentioning
confidence: 99%
“…A multiple alignment of PPase sequences from Eukarya (Arabidopsis, Beta, Acetabularia and Plasmodium), Bacteria (Rhodospirillum, Streptomyces and Thermotoga) and Archaea (Pyrobaculum, M. mazei Mvp1 and Mvp2) was performed (not shown) and conserved residues are shown in white on a black background in Figure 5. The greatest similarities between the Mvp2 sequence and the sequences of other proton-translocating PPases were detected within the hydrophilic loops III and VI with cytoplasmic orientation and the C-terminal tail, all of which are probably part of the substrate-binding and hydrolysis domain or contribute to it (Takasu et al 1997). Moreover, there are highly conserved Gly residues in Helices 3, 4, 5, 9, 13 and 15 that could be responsible for tight localization of the corresponding helices.…”
Section: Putative Enzyme Structure and Sequence Characteristicsmentioning
confidence: 97%
“…Moreover, antibody binding to the C-terminus inhibited PPi hydrolysis. Therefore, it was supposed that the C-terminus is close to the catalytic site of the cytoplasmic loop III (Takasu et al 1997). Considering the fundamental correspondence of the putative topology of Mvp1 and Mvp2 to that of other V-type PPases, a basic uniformity of secondary structure is most likely (Zhen et al 1997).…”
Section: Putative Enzyme Structure and Sequence Characteristicsmentioning
confidence: 99%
“…SDS/PAGE was performed in 12% gels. Immunoblotting was carried out with a poly(vinylidene difluoride) membrane (Millipore) by the standard procedure [19]. Protein A conjugated to horseradish peroxidase was used to detect the IgG on the immunoblot.…”
Section: Immunoblottingmentioning
confidence: 99%